Implementation of a Brain Training Pilot Study For People With Mild Cognitive Impairment. - Knoefel, Frank; Gaudet, Caroline; López Zunini, Rocio; Breau, Michael; Sweet, Lisa; Wallace, Bruce; Goubran, Rafik; Taler, Vanessa (Canadian Geriatrics Journal, 2018)
Objective A pilot study to determine the feasibility of recruiting patients with MCI to test for cognitive interventions. Method Thirty patients with amnestic MCI were to be divided into two intervention arms and one control group. Participants went to local sites and completed brain training for one hour three times per week for nine weeks. Outcome measures were: recruitment, computer abilities, compliance, task performance, neuropsychological tests, and electroencephalography. Results After six months, only 20 participants had been recruited. Seventeen were allocated to one of the two intervention groups. Compliance was good and computer skills were not an obstacle. Participants improved their abilities in the modules, but there were no statistically significant changes on neuropsychological tests or EEG. Conclusions Recruitment of MCI participants for extensive cognitive intervention is challenging, but achievable. This pilot study was not powered to detect clinical changes. Future trials should consider recruitment criteria, intervention duration, scheduling, and study location.